Organophosphorus chemical warfare agent simulant DMMP promotes structural reinforcement of urea-based chiral supramolecular gels. Issue 16 (23rd January 2015) - Piana, Francesca; Facciotti, Marco; Pileio, Giuseppe; Hiscock, Jennifer R.; Van Rossom, Wim; Brown, Richard C. D.; Gale, Philip A.
Abstract : The addition of a certain amount of organophosphorus chemical warfare agent simulant DMMP promotes strengthening of the urea-based supramolecular gel structure. Abstract : Six urea-based supramolecular gels have been obtained in situ by mixing either ( R )-(−)-1-(1-naphthyl)ethyl isocyanate or (±)-1-(1-naphthyl)ethyl isocyanate with various amines. This allowed a comparative study on the effects of chirality on the response of the molecular gels to the presence of the neutral organophosphate guest dimethyl methylphosphonate (DMMP). The inversion test results show that the absence of enantiomeric purity causes marked instability of the gel network in the presence of the guest. DSC and rheology measurements reveal the promotion of a structural reinforcement of the gels when 0.01 mL of DMMP interacts with the enantiomerically pure systems. This effect was investigated by means of electrostatic potential surface calculations and 31 P–{ 1 H} NMR spectroscopy.